Contextual Analysis of Battery Electric Vehicles’ Adoption in Italy - Federico Silvestri; Seyed Mahdi Miraftabzadeh; Michela Longo; Dario Zaninelli (Energies)
This study investigates the context in which the adoption of battery electric vehicles (BEVs) takes place in Italy. Several region-specific characteristics pertaining to socioeconomic conditions, transportation, and infrastructure are studied and combined by means of Principal Component Analysis (PCA) and k-means clustering. The model acts as a tool able to provide a 3D visualization of the relative states of the 20 regions analyzed. Three Principal Components are computed, and seven clusters are identified and described, with Lombardy, Trentino-South Tyrol, Aosta Valley, and Lazio showing an advanced level of adoption compared to the rest of Italy. Key findings indicate that regional incentives are necessary to accelerate adoption in underperforming regions, and that incentives targeting the scrapping of old vehicles might not always be useful. To address the emerging disparities, recommendations tailored to the individual territories are provided.